Association of serum and urinary uromodulin and their correlates in older adults—The Cardiovascular Health Study. Issue 7 (27th December 2019) - Steubl, Dominik; Buzkova, Petra; Ix, Joachim H.; Devarajan, Prasad; Bennett, Michael R.; Chaves, Paolo H. M.; Shlipak, Michael G.; Bansal, Nisha; Sarnak, Mark J.; Garimella, Pranav S.
Abstract: Uromodulin is released into serum (sUMOD) and urine (uUMOD) exclusively by renal tubular cells. Both sUMOD and uUMOD are correlated with estimated glomerular filtration rate (eGFR), and associated with mortality and cardiovascular disease (CVD). However, no study to our knowledge has measured both sUMOD and uUMOD in the same population, thus the relationship of sUMOD with uUMOD with one another, and their respective correlates have not been evaluated simultaneously. We evaluated the correlations of sUMOD, uUMOD with eGFR in a random sub‐cohort (n = 933) of the Cardiovascular Health Study and their associations with demographic and laboratory parameters and CVD risk factors using multi‐variable linear regression analysis. The mean age of the cohort was 78 years, 40% were male and 15% were Black. The mean sUMOD level was 127 ng/mL, uUMOD was 30 500 ng/mL and eGFR was 63 mL/min/1.73 m 2 . Correlation between sUMOD and uUMOD, adjusted for eGFR was moderate ( r = 0.27 [95% confidence interval = 0.21‐0.33]). The correlation of eGFR with sUMOD ( r = 0.44 [0.39‐0.49]) was stronger than with uUMOD ( r = 0.21 [0.15‐0.27]). In multi‐variable analysis adjusting sUMOD for uUMOD and vice versa, sUMOD was independently associated with eGFR ( β = 1.3 [1.1‐1.6]), log2 C‐reactive protein ( β = −4.2 [−6.8 to −1.6]) and male sex ( β = −13.6 [−22.7 to −4.5]). In contrast, male sex was associated with higher uUMOD ( β = 3700 [400‐7000]), while diabetes ( β = −6400 [−10 600 to −2100]) and hypertension (−4300 [−7500 to −1100]) were associated with lower uUMOD levels. We conclude that sUMOD is more strongly associated with eGFR compared with uUMOD. Correlates of sUMOD and uUMOD differ substantially, suggesting that apical and basolateral secretion may be differentially regulated. SUMMARY AT A GLANCE: Although both serum and urine uromodulin levels are correlated directly with eGFR, it is unclear which is better. In this study, serum uromodulin is more strongly associated with eGFR than urine uromodulin. In addition, correlates of serum and urine uromodulin differ, thus they may be differentially regulated to a certain extent.